Sexual Harassment and its Impact in Females at Workplace in Dhanusha District, Madhesh Province, Nepal - Jha, Lalan; Giri, Shree Shyam; Sah, Poonam; Kapar, Vijay Kumar; Yadav, Pramod Kumar (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: The violence of sexual harassment at workplace is problematic issue in the community for females. It has a direct bearing on the workplace productivity as well as the development of the society. Therefore, this study was conducted to assess the effects of sexual harassment on health and daily performances of female employees. MATERIALS AND METHODS: Descriptive study was carried out in Dhanusha district of Madhesh province of Nepal from March, 2022 to April 2022. The study was conducted in different organizations (workplace) situated in Dhanusha district which were selected purposely. The sample size was 120 working females. Banks, schools, hospitals, and shopping centres were the selected female working places in this study. Face to face interview was conducted through structured questionnaire for the 120 females who gave the permission for interview. RESULTS: The present study demonstrated that 61.67 % respondents exhibited to possess the knowledge about sexual harassment however, 38.33% of the female respondents demonstrated to be unaware about sexual harassment at their workplace. Among the total numbers of female participating in the research, 29% of the females had experienced the incidence of sexual harassment. Majority of respondents (25.71%) working efficacy had reduced after being suffered from sexual harassment and 5.71% had changed their job. 5.71% females suffered from headache and body ache, 5.71% suffered from high blood pressure, 22.86% suffered from anorexia, 20% suffered from restlessness/insomnia, 17.14% suffered from fatigue, 14.29% suffered from anxiety, 11.43% faced depression and 2.86% had lost their body weight. CONCLUSIONS: Sexual harassment for females at work place affects them physically as well as mentally. Therefore, awareness programme should be conducted time to time and anti-sexual harassment policy should be implemented at workplace.